2010
DOI: 10.3892/ijmm_00000496
|View full text |Cite
|
Sign up to set email alerts
|

The endocytic penetration mechanism of iron oxide magnetic nanoparticles with positively charged cover: A morphological approach

Abstract: Abstract. In this study we present a morphological approach in observing the interaction of cationic magnetic nanoparticles with A-549 cells (human lung adenocarcinoma). Under our experimental conditions, nanoparticles easily penetrated cells and were observed in vivo, using bright light microscopy. In fixed cells, nanoparticles remained inside cells, showing quantity and distribution patterns similar to those in unfixed cells. The presence of nanoparticles did not affect cell viability or the morphologic para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…This indicates once again the inverse toxicity of the FeNPs in cells of different functions. However, these genes demonstrated the endocytotic activity of two cells to the FeNPs, which agrees with the previous reports that the FeNPs were internalized into cells by endocytosis [54][55][56][57]. In addition to the phagosome pathway, the lysosome and notch signaling pathways were also enriched by the genes induced by ldFeNPs in the THP-1 cells ( Figure 10A).…”
Section: Pathway Analysis Of Fenp-responsive Genessupporting
confidence: 91%
“…This indicates once again the inverse toxicity of the FeNPs in cells of different functions. However, these genes demonstrated the endocytotic activity of two cells to the FeNPs, which agrees with the previous reports that the FeNPs were internalized into cells by endocytosis [54][55][56][57]. In addition to the phagosome pathway, the lysosome and notch signaling pathways were also enriched by the genes induced by ldFeNPs in the THP-1 cells ( Figure 10A).…”
Section: Pathway Analysis Of Fenp-responsive Genessupporting
confidence: 91%
“…Previous studies on NP uptake reported on clathrin-dependent endocytosis mechanisms as well as internalization by the macropinocytosis pathway in iron oxide or silver nanoparticles. 42 There was a slightly enhanced CD 90 expression and decreased CD 73 expression after ZnO-NP exposure compared to the control, but differences were not significant. located in the perinuclear cytoplasm whereas an intranuclear distribution could only be observed sporadically.…”
Section: Discussionmentioning
confidence: 62%
“… In regulation of cell activity, the vesicles from mitochondria were stimulated to act as the primary response to oxidative stress through delivering selected cargo to lysosomes . It has been proved that IRONs could be internalized through vesicles, which transferred the inner content to lysosome to degrade . In terms of cell communication, the vesicles secretion was strongly associated with ion channel between myocytes .…”
Section: Discussionmentioning
confidence: 99%
“…55 It has been proved that IRONs could be internalized through vesicles, which transferred the inner content to lysosome to degrade. 56 In terms of cell communication, the vesicles secretion was strongly associated with ion channel between myocytes. 57,58 The vesicles of cardiac cells in 3D environment due to incubation of DMSA-IRONs might involve in the modulation of cell communication, such as assembly of IDs between cardiac cells.…”
Section: Discussionmentioning
confidence: 99%